Denoising and reconstruction of evaporation duct based on quadratic optimal threshold approximation message passing method - Guosheng RUI; Ge LIU; Wenbiao TIAN; Daoguang DONG; Yanan ZHANG (Tongxin xuebao)
To solve the problem that the mixed noise of compressed sensing observation stage had adverse effects on the high-precision reconstruction in the time-space situation awareness process of evaporative duct,an approximate message passing method based on quadratic optimal threshold was proposed.A quadratic stabilization threshold function which integrated advantages of soft and hard threshold functions was designed,and the optimal threshold setting policy was added to the iterative process based on conjugate gradient method to speed up convergence.Theoretical analysis and experiments show that,compared with several mainstream algorithms,the proposed algorithm has the faster convergence rate and lower denoising reconstruction error.